Tin wire with anti-oxidation coating on the outside and no splashing and preparation method thereof
By introducing composite nanofibers and porous carbon structures into the coating of tin wire, the splashing problem during traditional tin wire welding is solved, the reliability and uniformity of welding products are improved, and the stability and efficiency of tin wire welding are achieved. .
Patent Information
- Application Number
- CN202211052392.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The flux is prone to splashing during traditional tin wire welding, resulting in short circuits and continuous welding problems in welding products, and it is difficult to ensure uniformity during automated welding.
Using tin wire with an anti-oxidation coating on the outside, the coating consists of a rosin mixture, film forming agent, cosolvent, surfactant and composite nanofibers. The composite nanofibers are prepared by electrospinning technology and porous are introduced into the coating. Carbon structure, forming a mesh structure to retain bubbles and reduce volatilization pressure.
It significantly reduces the splash phenomenon during tin wire welding, improves the reliability and uniformity of welding products, reduces bubble bursting and volatilization pressure after welding, and avoids short circuit and continuous welding problems.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic welding, in particular to a non-splashing tin wire with an anti-oxidation coating on the outside and a preparation method thereof. Background Art
[0002] Tin wire is an important industrial raw material for connecting electronic components in welding circuits. It is widely used in the electronics industry, home appliance manufacturing, automobile manufacturing, maintenance industry and daily life. Traditional tin wires are usually axial core structures, and the flux is in the core of the solder. When heating and welding, the solder layer melts and the flux flows out from the core, removing the oxide layer of the welded part to play a fluxing role and achieve welding. Because the flux is concentrated inside the solder, it is quickly melted and vaporized by the instantaneous high temperature of the electric soldering iron during welding, which can easily cause the flux and solder to splash, causing short circuits and continuous welding problems in the welded products. In addition, the microscopic uniformity of the core flux is difficult to accurately guarantee, which is easy to cause welding defects during the automated welding process.
[0003] In order to reduce the spatter phenomenon during tin wire welding, for example, the invention patent with announcement number CN106624442A discloses a high-toughness spatter-less self-protective coating flux-cored welding wire and its preparation method. The titanium dioxide in the coating increases the plasticity of the active material to make it easy to adhere to the welding wire. The low ionization voltage elements contained in the titanium dioxide and feldspar are conducive to arc stabilization and droplet refinement. The deoxidizer helps to deoxidize and dehydrogenate the weld and change the morphology of inclusions in the weld. The activator changes the stress state of the droplet, increases the droplet transition frequency, and refines the droplet, thereby achieving the effect of reducing the spatter rate. However, when the tin wire is welded, it is subjected to the instantaneous high temperature of the electroplating iron, and the coating will melt and vaporize rapidly, forming a large number of bubbles that are too large and too much, generating a large volatilization pressure, which will still cause the tin wire to spatter, causing the welded product to have problems such as short circuit and continuous welding. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a non-splashing tin wire with an anti-oxidation coating on the outside and a preparation method thereof, which reduces the generation of bubbles and lowers the volatilization pressure under instantaneous heating, thereby achieving the effect of reducing the splashing of the tin wire.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A tin wire with an anti-oxidation coating on the outside to prevent splashing, the tin wire comprising a tin wire matrix and a coating coated on the surface of the tin wire matrix, the tin wire matrix accounts for 97.8-98.6% of the mass percentage of the tin wire, and the coating accounts for 1.4-2.2% of the mass percentage of the tin wire, wherein the tin wire matrix is any one of Sn-0.7Cu, Sn-3.0Ag-0.5Cu, and Sn-0.3Ag-0.7Cu; the coating raw materials include, by weight: 70-80 parts of a rosin mixture, 0.5-1.3 parts of a film former, 5-10 parts of a cosolvent, 4-9 parts of a surfactant, and 2-5 parts of composite nanofibers.
[0007] As a further preferred embodiment of the present invention, the rosin mixture is composed of hydrogenated rosin alcohol, hydrogenated rosin resin, polymerized rosin, and rosin pentaerythritol ester in a mass ratio of 1: (1-2): (0.5-1.5): (0.3-0.8);
[0008] The film-forming agent is selected from at least one of polyacrylamide and polyethylene glycol;
[0009] The co-solvent is selected from at least one of anhydrous ethanol, methanol and acetone;
[0010] The surfactant is selected from at least one of dibromosuccinic acid, ethylenediamine hydrochloride, and 1,2-dibromoethylbenzene.
[0011] As a further preferred embodiment of the present invention, the preparation method of the composite nanofiber is as follows:
[0012] 1) Using 3,3',4,4'-biphenyltetracarboxylic dianhydride and p-phenylenediamine as solutes and N,N-dimethylacetamide as solvent, the solutes are sequentially added into the solvent at 150-190 r / min, and after being completely dissolved, reacting at 50-56° C. and 100-150 r / min in a nitrogen atmosphere for 6-8 hours to obtain a polyamic acid solution;
[0013] 2) Add appropriate amounts of silicon nitride and composite porous carbon to the polyamic acid solution in sequence, and obtain a spinning solution after ultrasonic dispersion. The spinning solution is subjected to electrostatic spinning, and the spinning product is placed in a blast oven, and heat-treated at 120-150°C, 180-230°C, and 300-320°C for 1-2 hours, respectively, and then immersed in the polyamic acid solution for 20-30 minutes. After taking out, keep it in an oven at 40-45°C for 3-5 hours to obtain composite nanofibers.
[0014] As a further preferred embodiment of the present invention, the usage ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride, p-phenylenediamine and N,N-dimethylacetamide is (14.3-15.2) g: (5.2-6.0) g: (120-135) g;
[0015] The addition amount of silicon nitride and composite porous carbon accounts for 2-4% and 1-2% of the mass of the polyamic acid solution respectively;
[0016] The parameters of the electrospinning are as follows: spinning voltage is 10-30KV, negative pressure is 0-10KV, solution propulsion speed is 0.3-2.0mL / h, spinning temperature is 15-45°C, spinning relative humidity is 30-80%, receiving device rotation speed is 100-200rpm, receiving distance is 5-15cm, and the swing rate of the spinning needle is 100-300cm / min.
[0017] As a further preferred embodiment of the present invention, the preparation method of the composite porous carbon is as follows:
[0018] 1) adding porous carbon to an ethanol aqueous solution, ultrasonically dispersing for 30-50 min, slowly dropping N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, adjusting the pH to 3.0-3.5 with hydrochloric acid to obtain solution A, then dissolving 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in the ethanol aqueous solution, mixing well to obtain solution B for standby use;
[0019] 2) Slowly add solution B to solution A to obtain a mixed solution, condense and reflux at 60-65° C., stir for 10-15 hours, and after the reaction is completed, centrifuge the product in a centrifuge, wash the product repeatedly with ethanol, put it in a vacuum drying oven, and dry it to obtain composite porous carbon.
[0020] Furthermore, in step 1), in the solution A, the ratio of the porous carbon, the ethanol aqueous solution, and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane is (2-5) g: (100-300) mL: (0.3-0.6) g;
[0021] In the ethanol aqueous solution, the volume ratio of ethanol to water is (3-4):1;
[0022] In the solution B, the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and ethanol aqueous solution is (2-4) g: (25-40) mL.
[0023] Furthermore, in step 2), in the mixed solution, the ratio of the porous carbon to 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid is (2-5) g: (2-4) g;
[0024] The centrifugal speed is 6000-8000r / min, and the centrifugation time is 5-10min;
[0025] The drying temperature is 110-120° C., and the drying time is 10-13 hours.
[0026] As a further preferred embodiment of the present invention, the preparation method of the porous carbon is as follows:
[0027] 1) zinc nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide are mixed and stirred at room temperature for 30-40 minutes, the resulting mixed solution is transferred to a reactor for heating reaction, cooled naturally to room temperature, filtered, and washed repeatedly with N,N-dimethylformamide, ethanol and chloroform alternately, and dried for use;
[0028] 2) The above product is placed in a tubular furnace, in an argon atmosphere, kept warm, cooled to room temperature, immersed in a sufficient amount of hydrochloric acid solution for acid etching for 20-50 minutes, taken out after the treatment, repeatedly washed with deionized water until neutral, and dried to obtain porous carbon.
[0029] As a further preferred embodiment of the present invention, the usage ratio of zinc nitrate hexahydrate, 2-aminoterephthalic acid, and N,N-dimethylformamide is (3-5) g: (0.6-1.2) g: (170-230) mL;
[0030] The heating reaction temperature is 110-120°C and the reaction time is 45-50h;
[0031] The temperature of the heat preservation treatment is 800-900°C, and the heat preservation time is 2-5h;
[0032] The heating rate of the heat preservation treatment is 1-3°C / min;
[0033] The concentration of the hydrochloric acid solution is 10-12 mol / L.
[0034] A method for preparing a tin wire with an anti-oxidation coating on the outside and no splashing, comprising the following steps:
[0035] 1) heating the alloy required for the tin wire matrix to a molten state, stirring and mixing, and then casting and cooling to obtain the tin wire matrix;
[0036] 2) placing the rosin mixture in a container, heating it to 80-90° C., stirring it until it is completely melted, stopping heating, sequentially adding a film-forming agent, a cosolvent, a surfactant, and composite nanofibers, stirring evenly, and cooling it to obtain a coating agent;
[0037] 3) The tin wire matrix and the coating agent are extruded and mixed, and then subjected to a wire drawing process to obtain the desired tin wire.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] In the present invention, the prepared polyamic acid solution is mixed with nano silicon nitride and composite porous carbon, and the composite nanofiber is prepared by using electrostatic spinning technology. After the composite nanofiber is subjected to high-temperature imidization, the polyamic acid solution is attached to the surface of the composite nanofiber by an immersion method, and the composite nanofiber is subjected to imidization again to obtain a composite nanofiber with a low thermal expansion coefficient. The composite nanofiber is added to a coating agent, extruded, mixed and drawn with a tin wire matrix, so as to form a coating on the surface of the tin wire matrix. The composite nanofiber introduced into the coating can reduce the expansion degree of the coating at high temperature, so that the bubbles generated by the rosin mixture in the coating after the tin wire is melted are not easy to be too large and too much, thereby reducing the splashing generated when the bubbles burst; at the same time, the composite nanofibers are interwoven and interconnected in the coating to form a mesh structure. The high-density mesh structure can intercept part of the large-particle splash generated when the bubbles burst, so that the large-particle splash is intercepted in the mesh structure, thereby significantly reducing the generation of splashing and improving the reliability of the post-weld product.
[0040] In order to further reduce the generation of spatter, in the present invention, a metal organic framework is used as a template, and the 2-aminoterephthalic acid ligand contained is calcined in argon and then etched with hydrochloric acid to obtain a porous carbon with a honeycomb structure. The porous carbon has a high porosity. After being introduced into the composite nanofiber, the composite nanofiber also presents a porous structure, so that a large number of mesopores and micropores exist in the coating on the surface of the tin wire substrate, which can release the pressure generated by the volatilization of the tin wire during welding, thereby further reducing the spatter of the tin wire. In addition, the composite nanofiber with a porous structure can provide space for volume expansion, thereby The volume expansion of the buffer bubble formation process can be further reduced to further reduce the splashing when the bubble bursts; at the same time, in order to improve the antioxidant properties of the coating and avoid the degradation of the coating performance due to oxidation, in the present invention, the porous carbon is loaded with an organic antioxidant to form a composite porous carbon. On the one hand, the antioxidant property of the composite nanofiber can be improved, so that the coating on the surface of the tin wire substrate has good antioxidant properties. On the other hand, the surface modification of the porous carbon with an organic antioxidant helps to improve the compatibility of the porous carbon with the polymer and reduce the agglomeration of the porous carbon, thereby helping to improve the comprehensive performance of the composite nanofiber.
[0041] In the present invention, a coating with good anti-oxidation performance is formed on the surface of the tin wire substrate. The presence of the coating not only makes it difficult for bubbles to be too large and too many after the tin wire is melted, thereby reducing the splashing generated when the bubbles burst, but also can intercept some large particles of splashing generated when the bubbles burst, and at the same time can release the pressure generated by the volatilization of the tin wire during welding, thereby effectively reducing the generation of splashing of the tin wire during welding and improving the reliability of the product after welding. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] A tin wire with an anti-oxidation coating on the outside to prevent splashing, comprising a tin wire matrix and a coating coated on the surface of the tin wire matrix, wherein the tin wire matrix accounts for 97.8% of the mass percentage of the tin wire, and the coating accounts for 2.2% of the mass percentage of the tin wire, wherein the tin wire matrix is Sn-0.7Cu; the coating raw materials include, by weight: 70 parts of rosin mixture, 0.5 parts of polyacrylamide, 5 parts of anhydrous ethanol, 4 parts of dibromosuccinic acid, and 2 parts of composite nanofibers;
[0045] The rosin mixture is composed of hydrogenated rosin alcohol, hydrogenated rosin resin, polymerized rosin, and rosin pentaerythritol ester in a mass ratio of 1:1:0.5:0.3;
[0046] The preparation method of the tin wire is as follows:
[0047] 1) heating the alloy required for the tin wire matrix to a molten state, stirring and mixing, and then casting and cooling to obtain the tin wire matrix;
[0048] 2) placing the rosin mixture in a container, heating it to 80° C., stirring it until it is completely melted, stopping heating, sequentially adding a film-forming agent, a cosolvent, a surfactant, and composite nanofibers, stirring them evenly, and cooling them to obtain a coating agent;
[0049] 3) The tin wire matrix and the coating agent are extruded and mixed, and then subjected to a wire drawing process to obtain the desired tin wire.
[0050] The above-mentioned method for preparing the composite nanofiber is as follows:
[0051] 1) Weigh 14.3 g of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 5.2 g of p-phenylenediamine as solutes, and weigh 120 g of N,N-dimethylacetamide as solvent. At 150 r / min, add the solutes to the solvent in sequence. After they are completely dissolved, react at 50° C. and 100 r / min in a nitrogen atmosphere for 6 hours to obtain a polyamic acid solution;
[0052] 2) Add appropriate amounts of silicon nitride and composite porous carbon to the polyamic acid solution in sequence, control the addition amounts of silicon nitride and composite porous carbon to account for 2% and 1% of the mass of the polyamic acid solution, and obtain a spinning solution after uniform ultrasonic dispersion. The spinning solution is subjected to electrostatic spinning, and the positive high voltage of the spinning is 10KV, the negative pressure is 0KV, the solution propulsion speed is 0.3mL / h, the spinning temperature is 15°C, the spinning relative humidity is 30%, the receiving device speed is 100rpm, the receiving distance is 5cm, the swing rate of the spinning needle is 100cm / min, and the spinning product is placed in a blast oven, and heat-treated at 120°C, 180°C and 300°C for 1h respectively, and then immersed in the polyamic acid solution for 20min, taken out and heat-treated in an oven at 40°C for 3h to obtain composite nanofibers.
[0053] The preparation method of the composite porous carbon is as follows:
[0054] 1) Add 2 g of porous carbon to 100 mL of ethanol aqueous solution, disperse ultrasonically at 300 W for 30 min, slowly dropwise add 0.3 g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, adjust the pH to 3.0 with hydrochloric acid to obtain solution A, then dissolve 2 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in 25 mL of ethanol aqueous solution, mix well to obtain solution B, which is set aside, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 3:1;
[0055] 2) Solution B is slowly added dropwise to solution A to obtain a mixed solution, which is condensed and refluxed at 60°C and stirred for 10 hours. After the reaction is completed, the product is placed in a centrifuge and centrifuged at 6000 r / min for 5 minutes. The product is repeatedly washed with ethanol and placed in a vacuum drying oven and dried at 110°C for 10 hours to obtain a composite porous carbon.
[0056] The preparation method of porous carbon is as follows:
[0057] 1) 3 g of zinc nitrate hexahydrate, 0.6 g of 2-aminoterephthalic acid and 170 mL of N,N-dimethylformamide were mixed and stirred at 100 r / min for 30 min at room temperature, the resulting mixed solution was transferred to a reactor, heated at 110° C. for reaction for 45 h, cooled naturally to room temperature, filtered, and washed alternately with N,N-dimethylformamide, ethanol and chloroform, and dried for later use;
[0058] 2) Place the above product in a tubular furnace, heat it to 800°C at 1°C / min in an argon atmosphere, and keep it warm for 2 hours. After cooling to room temperature, immerse it in a sufficient amount of 10 mol / L hydrochloric acid solution for acid etching for 20 minutes. After the treatment is completed, take it out, wash it repeatedly with deionized water until it is neutral, and dry it at 60°C to constant weight to obtain porous carbon.
[0059] Example 2
[0060] A tin wire with an anti-oxidation coating on the outside to prevent splashing, comprising a tin wire matrix and a coating coated on the surface of the tin wire matrix, wherein the tin wire matrix accounts for 98.2% of the mass percentage of the tin wire, and the coating accounts for 1.8% of the mass percentage of the tin wire, wherein the tin wire matrix is Sn-3.0Ag-0.5Cu; the coating raw materials include, by weight: 75 parts of rosin mixture, 1.1 parts of polyethylene glycol, 7 parts of methanol, 5 parts of ethylenediamine hydrochloride, and 3 parts of composite nanofibers;
[0061] The rosin mixture is composed of hydrogenated rosin alcohol, hydrogenated rosin resin, polymerized rosin, and rosin pentaerythritol ester in a mass ratio of 1:1.5:1:0.5;
[0062] The preparation method of the tin wire is as follows:
[0063] 1) heating the alloy required for the tin wire matrix to a molten state, stirring and mixing, and then casting and cooling to obtain the tin wire matrix;
[0064] 2) placing the rosin mixture in a container, heating it to 85° C., stirring it until it is completely melted, stopping heating, sequentially adding a film-forming agent, a cosolvent, a surfactant, and composite nanofibers, stirring them evenly, and cooling them to obtain a coating agent;
[0065] 3) The tin wire matrix and the coating agent are extruded and mixed, and then subjected to a wire drawing process to obtain the desired tin wire.
[0066] The above-mentioned method for preparing the composite nanofiber is as follows:
[0067] 1) Weigh 14.8 g of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 5.7 g of p-phenylenediamine as solutes, and weigh 128 g of N,N-dimethylacetamide as solvent. At 180 r / min, add the solutes into the solvent in sequence. After they are completely dissolved, react at 53° C. and 120 r / min in a nitrogen atmosphere for 7 hours to obtain a polyamic acid solution;
[0068] 2) Add appropriate amounts of silicon nitride and composite porous carbon to the polyamic acid solution in sequence, control the addition amounts of silicon nitride and composite porous carbon to account for 3% and 1.5% of the mass of the polyamic acid solution, and obtain a spinning solution after uniform ultrasonic dispersion. The spinning solution is subjected to electrostatic spinning, and the positive high voltage of the spinning is 20KV, the negative pressure is 5KV, the solution propulsion speed is 1.5mL / h, the spinning temperature is 40°C, the spinning relative humidity is 50%, the receiving device speed is 150rpm, the receiving distance is 10cm, the swing rate of the spinning needle is 200cm / min, and the spinning product is placed in a blast oven, and heat-treated at 130°C, 210°C and 310°C for 1.5h respectively, and then immersed in a polyamic acid solution for 25min. After taking out, it is heat-treated in an oven at 42°C for 4h to obtain composite nanofibers.
[0069] The preparation method of the composite porous carbon is as follows:
[0070] 1) Add 3 g of porous carbon to 200 mL of ethanol aqueous solution, disperse ultrasonically at 400 W for 40 min, slowly dropwise add 0.5 g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, adjust the pH to 3.2 with hydrochloric acid to obtain solution A, then dissolve 3 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in 35 mL of ethanol aqueous solution, mix well to obtain solution B, which is set aside, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 3.5:1;
[0071] 2) Solution B was slowly added dropwise to solution A to obtain a mixed solution, which was condensed and refluxed at 62°C and stirred for 13 hours. After the reaction was completed, the product was placed in a centrifuge and centrifuged at 7000 r / min for 8 minutes. The product was repeatedly washed with ethanol and placed in a vacuum drying oven and dried at 115°C for 12 hours to obtain a composite porous carbon.
[0072] The preparation method of porous carbon is as follows:
[0073] 1) 4 g of zinc nitrate hexahydrate, 1.0 g of 2-aminoterephthalic acid and 200 mL of N,N-dimethylformamide were mixed and stirred at 150 r / min for 35 min at room temperature, the resulting mixed solution was transferred to a reactor, heated at 115° C. for reaction for 48 h, cooled naturally to room temperature, filtered, and washed alternately with N,N-dimethylformamide, ethanol and chloroform, and dried for later use;
[0074] 2) The above product is placed in a tubular furnace, and in an argon atmosphere, the temperature is increased to 850°C at 2°C / min, and kept warm for 3 hours. After cooling to room temperature, it is immersed in a sufficient amount of 11 mol / L hydrochloric acid solution for acid etching for 35 minutes. After the treatment is completed, it is taken out, repeatedly washed with deionized water until neutral, and dried at 70°C to constant weight to obtain porous carbon.
[0075] Example 3
[0076] A tin wire with an anti-oxidation coating on the outside to prevent splashing, comprising a tin wire matrix and a coating coated on the surface of the tin wire matrix, wherein the tin wire matrix accounts for 98.6% of the mass percentage of the tin wire, and the coating accounts for 1.4% of the mass percentage of the tin wire, wherein the tin wire matrix is Sn-0.3Ag-0.7Cu; the coating raw materials include, by weight: 80 parts of a rosin mixture, 1.3 parts of polyacrylamide, 10 parts of acetone, 9 parts of 1,2-dibromoethylbenzene, and 5 parts of composite nanofibers;
[0077] The rosin mixture is composed of hydrogenated rosin alcohol, hydrogenated rosin resin, polymerized rosin, and rosin pentaerythritol ester in a mass ratio of 1:2:1.5:0.8;
[0078] The preparation method of the tin wire is as follows:
[0079] 1) heating the alloy required for the tin wire matrix to a molten state, stirring and mixing, and then casting and cooling to obtain the tin wire matrix;
[0080] 2) placing the rosin mixture in a container, heating it to 90° C., stirring it until it is completely melted, stopping heating, sequentially adding a film-forming agent, a cosolvent, a surfactant, and composite nanofibers, stirring them evenly, and cooling them to obtain a coating agent;
[0081] 3) The tin wire matrix and the coating agent are extruded and mixed, and then subjected to a wire drawing process to obtain the desired tin wire.
[0082] The above-mentioned method for preparing the composite nanofiber is as follows:
[0083] 1) Weigh 15.2 g of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and 6.0 g of p-phenylenediamine as solutes, and weigh 135 g of N,N-dimethylacetamide as solvent. At 190 r / min, add the solutes into the solvent in sequence. After they are completely dissolved, react at 56° C. and 150 r / min in a nitrogen atmosphere for 8 h to obtain a polyamic acid solution;
[0084] 2) Add appropriate amounts of silicon nitride and composite porous carbon to the polyamic acid solution in sequence, control the addition amounts of silicon nitride and composite porous carbon to account for 4% and 2% of the mass of the polyamic acid solution, and obtain a spinning solution after uniform ultrasonic dispersion. The spinning solution is subjected to electrostatic spinning, and the positive high voltage of the spinning is 30KV, the negative pressure is 10KV, the solution propulsion speed is 2.0mL / h, the spinning temperature is 45°C, the spinning relative humidity is 80%, the receiving device speed is 200rpm, the receiving distance is 15cm, and the swing rate of the spinning needle is 300cm / min. The spinning product is placed in a blast oven, and heat-treated at 150°C, 230°C and 320°C for 2h respectively, and then immersed in a polyamic acid solution for 30min. After taking out, it is heat-treated in an oven at 45°C for 5h to obtain composite nanofibers.
[0085] The preparation method of the composite porous carbon is as follows:
[0086] 1) Add 5 g of porous carbon to 300 mL of ethanol aqueous solution, disperse ultrasonically at 500 W for 50 min, slowly dropwise add 0.6 g of N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, adjust the pH to 3.5 with hydrochloric acid to obtain solution A, then dissolve 4 g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in 40 mL of ethanol aqueous solution, mix well to obtain solution B, which is set aside, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 4:1;
[0087] 2) Solution B is slowly added dropwise to solution A to obtain a mixed solution, which is condensed and refluxed at 65°C and stirred for 15 hours. After the reaction is completed, the product is placed in a centrifuge and centrifuged at 8000 r / min for 10 minutes. The product is repeatedly washed with ethanol and placed in a vacuum drying oven, and dried at 120°C for 13 hours to obtain a composite porous carbon.
[0088] The preparation method of porous carbon is as follows:
[0089] 1) 5 g of zinc nitrate hexahydrate, 1.2 g of 2-aminoterephthalic acid and 230 mL of N,N-dimethylformamide were mixed and stirred at 160 r / min for 40 min at room temperature, and the resulting mixed solution was transferred to a reactor, heated at 120° C. for reaction for 50 h, cooled naturally to room temperature, filtered, and washed alternately with N,N-dimethylformamide, ethanol and chloroform, and dried for later use;
[0090] 2) Place the above product in a tubular furnace, heat it to 900°C at 3°C / min in an argon atmosphere, and keep it warm for 5 hours. After cooling to room temperature, immerse it in a sufficient amount of 12 mol / L hydrochloric acid solution for acid etching for 50 minutes. After the treatment is completed, take it out, wash it repeatedly with deionized water until it is neutral, and dry it at 80°C to constant weight to obtain porous carbon.
[0091] Comparative Example 1: This comparative example is basically the same as Example 1, except that the coating does not contain composite nanofibers.
[0092] Comparative Example 2: This comparative example is basically the same as Example 1, except that no composite porous carbon is added during the preparation of the composite nanofibers.
[0093] Comparative Example 3: This comparative example is basically the same as Example 1, except that, in the preparation process of the composite nanofiber, porous carbon is used instead of composite porous carbon.
[0094] Test experiment:
[0095] The welding spatter rate of the tin wires prepared in Examples 1-3 and Comparative Examples 1-3 was evaluated by using GB / T25776-2010 "Welding Material Welding Process Performance Evaluation Method" to evaluate the welding spatter rate of the tin wire. The welding process parameters used were: welding current 200A, welding voltage 30V, welding speed 15cm / min, shielding gas 98%Ar+2%O2, gas flow rate 15L / min. The data comparison of each embodiment and comparative example is shown in Table 1.
[0096] Table 1
[0097] Example 1 Example 2 Example 3 Welding spatter rate % 0.23 0.21 0.26 Comparative Example 1 Comparative Example 2 Comparative Example 3 Welding spatter rate % 5.3 3.1 1.8
[0098] It can be seen from Table 1 that the tin wire in the present invention has excellent welding performance, can effectively reduce the generation of welding spatter, and meets the performance requirements of the solder wire in practical applications.
[0099] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A tin wire with an anti-oxidation coating on the outside to prevent splashing, characterized in that: The tin wire comprises a tin wire matrix and a coating coated on the surface of the tin wire matrix, wherein the mass percentage of the tin wire matrix is 97.8-98.6% of the tin wire, and the mass percentage of the coating is 1.4-2.2% of the tin wire, wherein the tin wire matrix is any one of Sn-0.7Cu, Sn-3.0Ag-0.5Cu, and Sn-0.3Ag-0.7Cu; the coating raw materials comprise, by weight: 70-80 parts of a rosin mixture, 0.5-1.3 parts of a film former, 5-10 parts of a cosolvent, 4-9 parts of a surfactant, and 2-5 parts of composite nanofibers; The preparation method of the composite nanofiber is as follows: 1) Using 3,3',4,4'-biphenyltetracarboxylic dianhydride and p-phenylenediamine as solutes and N,N-dimethylacetamide as solvent, the solutes are sequentially added into the solvent at 150-190 r / min, and after being completely dissolved, reacting at 50-56° C. and 100-150 r / min in a nitrogen atmosphere for 6-8 hours to obtain a polyamic acid solution; 2) Add appropriate amounts of silicon nitride and composite porous carbon to the polyamic acid solution in sequence, and obtain a spinning solution after ultrasonic dispersion, electrospin the spinning solution, put the spinning product into a blast oven, and heat-treat at 120-150° C., 180-230° C., and 300-320° C. for 1-2 hours, respectively, and then immerse it in the polyamic acid solution for 20-30 minutes, take it out, and heat-treat it in an oven at 40-45° C. for 3-5 hours to obtain composite nanofibers; The preparation method of the composite porous carbon is as follows: 1) adding porous carbon to an ethanol aqueous solution, ultrasonically dispersing for 30-50 min, slowly dropping N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, adjusting the pH to 3.0-3.5 with hydrochloric acid to obtain solution A, then dissolving 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in the ethanol aqueous solution, mixing well to obtain solution B for standby use; 2) Slowly add solution B to solution A to obtain a mixed solution, condense and reflux at 60-65° C., stir for 10-15 hours, and after the reaction is completed, centrifuge the product in a centrifuge, wash the product repeatedly with ethanol, put it in a vacuum drying oven, and dry it to obtain composite porous carbon.
2. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 1, characterized in that: The rosin mixture is composed of hydrogenated rosin alcohol, hydrogenated rosin resin, polymerized rosin, and rosin pentaerythritol ester in a mass ratio of 1: (1-2): (0.5-1.5): (0.3-0.8); The film-forming agent is selected from at least one of polyacrylamide and polyethylene glycol; the cosolvent is selected from at least one of anhydrous ethanol, methanol and acetone; the surfactant is selected from at least one of dibromosuccinic acid, ethylenediamine hydrochloride and 1,2-dibromoethylbenzene.
3. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 1, characterized in that: The usage ratio of the 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, p-phenylenediamine and N,N-dimethylacetamide is (14.3-15.2) g: (5.2-6.0) g: (120-135) g; the addition amount of the silicon nitride and the composite porous carbon accounts for 2-4% and 1-2% of the mass of the polyamic acid solution respectively; The parameters of the electrospinning are as follows: spinning voltage is 10-30KV, negative pressure is 0-10KV, solution propulsion speed is 0.3-2.0mL / h, spinning temperature is 15-45°C, spinning relative humidity is 30-80%, receiving device rotation speed is 100-200rpm, receiving distance is 5-15cm, and the swing rate of the spinning needle is 100-300cm / min.
4. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 1, characterized in that: In step 1), in the solution A, the ratio of the porous carbon, the ethanol aqueous solution, and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane is (2-5) g: (100-300) mL: (0.3-0.6) g; In the solution B, the ratio of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to ethanol aqueous solution is (2-4) g: (25-40) mL; In the ethanol aqueous solution, the volume ratio of ethanol to water is (3-4):
1.
5. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 1, characterized in that: In step 2), in the mixed solution, the ratio of the porous carbon to 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid is (2-5) g: (2-4) g; The centrifugal speed is 6000-8000r / min, and the centrifugation time is 5-10min; The drying temperature is 110-120° C., and the drying time is 10-13 hours.
6. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 1, characterized in that: The preparation method of the porous carbon is as follows: 1) zinc nitrate hexahydrate, 2-aminoterephthalic acid and N,N-dimethylformamide are mixed and stirred at room temperature for 30-40 minutes, the resulting mixed solution is transferred to a reactor for heating reaction, cooled naturally to room temperature, filtered, and washed repeatedly with N,N-dimethylformamide, ethanol and chloroform alternately, and dried for use; 2) The above product is placed in a tubular furnace, in an argon atmosphere, kept warm, cooled to room temperature, immersed in a sufficient amount of hydrochloric acid solution for acid etching for 20-50 minutes, taken out after the treatment, repeatedly washed with deionized water until neutral, and dried to obtain porous carbon.
7. The tin wire with an anti-oxidation coating on the outside and no splashing according to claim 6, characterized in that: The usage ratio of zinc nitrate hexahydrate, 2-aminoterephthalic acid, and N,N-dimethylformamide is (3-5) g: (0.6-1.2) g: (170-230) mL; The temperature of the heating reaction is 110-120°C, and the reaction time is 45-50h; the temperature of the heat preservation treatment is 800-900°C, and the heat preservation time is 2-5h; The heating rate of the heat preservation treatment is 1-3°C / min; the concentration of the hydrochloric acid solution is 10-12 mol / L.
8. A method for preparing a non-splashing tin wire with an anti-oxidation coating on the outside according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) heating the alloy required for the tin wire matrix to a molten state, stirring and mixing, and then casting and cooling to obtain the tin wire matrix; 2) placing the rosin mixture in a container, heating it to 80-90° C., stirring it until it is completely melted, stopping heating, sequentially adding a film-forming agent, a cosolvent, a surfactant, and composite nanofibers, stirring evenly, and cooling it to obtain a coating agent; 3) The tin wire matrix and the coating agent are extruded and mixed, and then subjected to a wire drawing process to obtain the desired tin wire.
